Writing by No Longer Writing: Kittler's mediatic approach to modern writing - Margot Mellet (Imaginations: Journal of Cross-Cultural Media Studies)
This article explores the concept of "de-writing," which involves suspending writing, diverting it in order to better understand it in a research-creation approach. De-writing is then considered as a new regime of the act of writing, particularly in connection with digital media culture. The article analyzes the mediatic and ontological change of writing through the work of Friedrich Kittler. It examines how writing in collaboration with the machine calls into question the notions of originality and the primacy of the human in creativity. As an epistemological and performative model, the article introduces the idea of "misuse," where a use of a tool, format, or medium deviating from the use initially intended, allows to explore new modes of writing.